2016
DOI: 10.1212/wnl.0000000000002770
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic profiling identifies an immune-related risk signature for glioblastoma

Abstract: We profiled the immune status in glioma and established a local immune signature for GBM, which could independently identify patients with a high risk of reduced survival, indicating the relationship between prognosis and local immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
162
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 35 publications
10
162
0
Order By: Relevance
“…Although typically used to define immunosuppressive TAMs, we find that the number of cells expressing CD163 in glioma tissue is significantly increased in patients with both grade I astrocytoma and GBM. This is supported by previous findings showing that the number of tumor associated macrophages may be less significant than their gene expression and corresponding functions, 64,65 and suggests that identification of additional markers is required to define a phenotype associated with immunosuppressive functions. This model is supported by the various redundant mechanisms of immunosuppression in the TME, including soluble GBM tumor cell derived factors such as TGFβ, 66 LDH5, 5 IL-10, 67 and IDO.…”
Section: Discussionsupporting
confidence: 84%
“…Although typically used to define immunosuppressive TAMs, we find that the number of cells expressing CD163 in glioma tissue is significantly increased in patients with both grade I astrocytoma and GBM. This is supported by previous findings showing that the number of tumor associated macrophages may be less significant than their gene expression and corresponding functions, 64,65 and suggests that identification of additional markers is required to define a phenotype associated with immunosuppressive functions. This model is supported by the various redundant mechanisms of immunosuppression in the TME, including soluble GBM tumor cell derived factors such as TGFβ, 66 LDH5, 5 IL-10, 67 and IDO.…”
Section: Discussionsupporting
confidence: 84%
“…However, EV uptake by a certain cell may not only depend on the presence of specific cellular receptors, but in the case of bridging uptake mechanisms, also on the availability of adaptor ligands, either secreted by the recipient or donor cell, or by other cells in the microenvironment. Here, we show that CCL18 functions as bridging adaptor for GBM EVs, and CCL18 expression has been identified as an important prognostic factor in GBM [90]. Recently, it was shown that EVs can also be decorated by autotaxin resulting in binding to integrins expressed on cell surfaces [32].…”
Section: Discussionmentioning
confidence: 95%
“…GO analysis showed that up-regulation genes were enriched in immune response and inflammatory response pathways. Moreover, it reported that immune response may play important role in GBM recently [17]. IKBIP (I kappa B kinase interacting protein) is a novel p53 target gene with proapoptotic function which is consistence with P53 pathway of GSEA results.…”
Section: Discussionmentioning
confidence: 99%